Clothing and embroidery. - 3G Elearning FZ LLC (United Arab Emirates : 3G Elearning FZ LLC, 2016)
This book will introduce to you the clothing and embroidery. It will presents the different types of clothing fabrics and embroidery. It will also helps you on how to start a business in clothing and embroidery industry.
Includes bibliographical references.
In English text.
Keywords: Embroidery -- Technique; Embroidery -- Design; Embroidery -- Patterns; Embroidery